2018
DOI: 10.1111/gcb.14123
|View full text |Cite|
|
Sign up to set email alerts
|

Land use intensity, rather than plant species richness, affects the leaching risk of multiple nutrients from permanent grasslands

Abstract: The intensification of land use constitutes one of the main drivers of global change and alters nutrient fluxes on all spatial scales, causing landscape-level eutrophication and contamination of natural resources. Changes in soil nutrient concentrations are thus indicative for crucial environmental issues associated with intensive land use. We measured concentrations of NO -N, NH -N, P, K, Mg, and Ca using 1,326 ion-exchange resin bags buried in 20 cm depth beneath the main root zone in 150 temperate grassland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 62 publications
4
24
0
2
Order By: Relevance
“…Besides an economic impact, grassland renewal has an environmental impact. Many studies show an increased emission of the greenhouse gasses N 2 O and CO 2 and leaching of nitrogen after ploughing grassland [8,[56][57][58][59][60][61][62]. Our study confirms that when grasslands contain at least 70% desirable grasses (i.e., Lolium perenne and Phleum pratense), long-term grass productivity does not increase and the NY N0 even decreases as a result of grassland renewal.…”
Section: Practical Implicationssupporting
confidence: 80%
“…Besides an economic impact, grassland renewal has an environmental impact. Many studies show an increased emission of the greenhouse gasses N 2 O and CO 2 and leaching of nitrogen after ploughing grassland [8,[56][57][58][59][60][61][62]. Our study confirms that when grasslands contain at least 70% desirable grasses (i.e., Lolium perenne and Phleum pratense), long-term grass productivity does not increase and the NY N0 even decreases as a result of grassland renewal.…”
Section: Practical Implicationssupporting
confidence: 80%
“…Furthermore, simple plant communities consisting of 12 plant species are more likely to regenerate than more complex communities consisting of 60 plant species. We also found that low‐intensity grasslands had a larger relative increase of released NO 3 ‐N compared with grasslands with high land‐use intensity, which was very likely caused by the already high release of NO 3 ‐N in grasslands with high land‐use intensity even without the presence of a disturbance (Klaus, Kleinebecker, et al, ).…”
Section: Discussionmentioning
confidence: 54%
“…Previous work on this experiment has shown that sward disturbance increases cover of bare soil, seedling species richness and number of seedlings directly after disturbance, due to the activation of the soil seed bank (Klaus et al, ) and release of nitrate (Klaus, Kleinebecker, et al, ). In the present study, we investigated how the disturbance effects and the recovery of ecosystem functions are related to land‐use intensity, plant species richness and functional composition in the first and second season after the sward disturbance.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Land-use intensification is one of the main drivers altering plant community composition (Matson et al 1997) for example by favouring the dominance of exploitative/acquisitive over conservative plant species due to the elevation of nutrient availability (Klaus et al 2018).…”
Section: Introductionmentioning
confidence: 99%